Health sector development in the Caribbean : socio-economic and political context (1960-1995) - Theodore, Karl ([s.n.] [S.l.], 1995)
Provides a historical overview of developments in health service delivery systems in the Caribbean during the period 1960-1995, with the independence era being taken to be 1960-1980.